Child's dental fear: Cause related factors and the influence of audiovisual modeling - Jayanthi Mungara; Madhulika Injeti; Elizabeth Joseph; Arun Elangovan; Rajendran Sakthivel; Girija Selvaraju (Wolters Kluwer Medknow Publications, 2013)
Background: Delivery of effective dental treatment to a child patient requires thorough knowledge to recognize dental fear and its management by the application of behavioral management techniques. Children's Fear Survey Schedule - Dental Subscale (CFSS-DS) helps in identification of specific stimuli which provoke fear in children with regard to dental situation. Audiovisual modeling can be successfully used in pediatric dental practice. Aim: To assess the degree of fear provoked by various stimuli in the dental office and to evaluate the effect of audiovisual modeling on dental fear of children using CFSS-DS. Materials and Methods: Ninety children were divided equally into experimental (group I) and control (group II) groups and were assessed in two visits for their degree of fear and the effect of audiovisual modeling, with the help of CFSS-DS. Results: The most fear-provoking stimulus for children was injection and the least was to open the mouth and having somebody look at them. There was no statistically significant difference in the overall mean CFSS-DS scores between the two groups during the initial session (P > 0.05). However, in the final session, a statistically significant difference was observed in the overall mean fear scores between the groups (P < 0.01). Significant improvement was seen in group I, while no significant change was noted in case of group II. Conclusion: Audiovisual modeling resulted in a significant reduction of overall fear as well as specific fear in relation to most of the items. A significant reduction of fear toward dentists, doctors in general, injections, being looked at, the sight, sounds, and act of the dentist drilling, and having the nurse clean their teeth was observed.